Analisa Hasil Pengujian Uprating Peralatan Pemutus Tenaga (PMT) 500 kV 7a3 Di Gardu Induk Tegangan Ekstra Tinggi New Balaraja - M Nur Rois Abid (Sutet, 2019)
In meeting customer needs while maintaining the stability of the power system, PT. PLN (Persero) conducted an acceleration program carried out on the generation system which was followed by upgrading of the main technical material (MTU) found in several substations both on 500 kV and 150 kV systems. One of the MTUs conducted by Uprating is a Circuit Breaker (CB) equipment 500 kV located in the New Balaraja Extra High Voltage Substation (GITET). The difference in manufacturer's brand is an obstacle to the Uprating process so that it needs to be done Wiring Modification. The test equipment performed is the quality of SF6 gas, insulation and contact resistance, CB opening and closing time, minimum coil voltage and capacitance testing that refers to applicable standards and then analyzed the results of tests with existing theories.